Decreased choriocapillaris perfusion following surgical excision of choroidal neovascular membranes in age-related macular degeneration. Issue 6 (1st June 1997) - Nasir, Ma'an A; Sugino, Ilene; Zarbin, Marco A
Abstract : AIMS/BACKGROUND: To evaluate macular changes following surgical excision of subfoveal choroidal neovascular membranes (CNVs) in age-related macular degeneration (AMD). METHODS: The clinical records, fluorescein angiograms, and CNV histopathology of 12 patients with AMD who underwent surgical excision of subfoveal CNV were reviewed. RESULTS: New areas of decreased choriocapillaris perfusion were noted by fluorescein angiography in the previous location of the CNV in 8/12 (75%) cases. Surgically excised tissue contained retinal pigment epithelium (RPE) in 11/11 specimens and choriocapillaris in 1/11 specimen studied. CONCLUSIONS: Choriocapillaris atrophy may partly underlie the limited visual outcome following subfoveal surgery for AMD. Abnormal choriocapillaris perfusion following CNV excision may be due to pre-existing choriocapillaris atrophy, to choriocapillaris damage or removal at the time of surgery, or to RPE removal at surgery with abnormal RPE repopulation of the dissected area and subsequent choriocapillaris degeneration.